The Beau Street, Bath Hoard - Anthony, Verity,; Abdy, Richard Anthony,; Clews, Stephen, (Archaeopress Roman archaeology ;, 2019)
The remarkable discovery of the Beau Street Hoard captured the public imagination and became the focus for a major scientific investigation and a significant learning and public engagement programme. This book provides a thorough and complete publication and analysis of the hoard, which is one of the largest yet found in a Roman town in Britain.